DATA-DRIVEN HR: USING ANALYTICS TO SHAPE YOUR PEOPLE STRATEGY - Syafrul Bahri; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This document outlines a comprehensive framework for leveraging people analytics to transform the HR function into a strategic asset. It argues that success is contingent upon two foundational pillars: robust data governance and the systematic upskilling of HR Business Partners (HRBPs). Effective data governance establishes a single source of truth through data standardization and integration while ensuring ethical compliance and data privacy, thereby creating a reliable and trusted data foundation. Concurrently, HRBPs must be equipped with data fluency, moving beyond basic literacy to interpret analytics, generate insights, and translate them into actionable business strategy. This dual approach ensures that data is not only accurate and secure but is also effectively communicated and applied. The synthesis of a disciplined data environment and a data-fluent HR workforce bridges the gap between analytical potential and tangible business outcomes, enabling evidence-based decision-making and fostering a proactive, strategic organizational culture.